2023
DOI: 10.1002/cbdv.202300179
|View full text |Cite
|
Sign up to set email alerts
|

Date Seeds (Phoenix dactylifera): Antioxidant Potential and Profile of Free and Bound Polyphenols from Different Cultivars

Abstract: In this study, the antioxidant activities and detailed phenolic profiling of extracts from seven cultivars of date seeds were investigated. Significant differences were detected among cultivars. Total phenolic content (TP) ranged between 135.9±12.1 and 284.86±21.9 mg GAE/g DM. The total flavonoid value varied between 34.20±0.34 and 94.46±1.04 mg RE/g DM. The condensed tannin ranged from 24.17±1.13 to 201.60±9.95 mg CTE/g DM. Phloroglucinolysis was used to depolymerize the bound polyphenols. Results show the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(91 reference statements)
2
2
0
Order By: Relevance
“…These differences from previous works can be due to the different extraction methods and studied cultivars. For example, the catechin content in the present work was around 1.5- and 3.8-fold of that reported by other authors ( Bettaieb et al, 2023 ; Ranasinghe et al, 2023 ; Muñoz-Tebar et al, 2024 ). However, generally, authors reported (poly)phenols of free fraction and rarely in insoluble-bound fraction.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…These differences from previous works can be due to the different extraction methods and studied cultivars. For example, the catechin content in the present work was around 1.5- and 3.8-fold of that reported by other authors ( Bettaieb et al, 2023 ; Ranasinghe et al, 2023 ; Muñoz-Tebar et al, 2024 ). However, generally, authors reported (poly)phenols of free fraction and rarely in insoluble-bound fraction.…”
Section: Resultssupporting
confidence: 63%
“…Although other authors have reported the main (poly)phenol to be catechin, benzoic acid, or p -coumaric ( Bouhlali et al, 2020 ; Ranasinghe et al, 2023 ; Muñoz-Tebar et al, 2024 ), the profile is in agreement with previous reports on date palm ( Ghnimi et al, 2017 ). Moreover, the abundance of flavan-3-ols has been previously reported by Djaoudene et al (2021) in different Algerian cultivars of date seeds ( P. dactylifera L.), who reported four procyanidins (trimeric and dimeric and B1, B2, and B2 3-O-gallate), and Bettaieb et al, 2023 , who detected two dimeric and three trimeric procyanidins. Hilary et al (2020) also detected five procyanidins, mainly dimers and trimers of type B, and different classes of caffeoyl shikimic acids and glycosylated quercetins in date seeds of the Khalas variety.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The modified Folin‐Ciocalteu method as described by Bettaieb et al., [74] was assessed to evaluate the total polyphenol content. The reaction mixture consisted of 100 μl of each extract (5 %), 0.5 ml Folin‐Ciocalteu reagent (1/10 in water) and 4 ml sodium carbonate solution (Na 2 CO 3 , 1 M).…”
Section: Methodsmentioning
confidence: 99%